2003
DOI: 10.4141/a02-095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pelleting and enzyme supplementation on variation in feed value of wheat-based diets fed to broiler chicks

Abstract: Scott, T. A., Silversides, F. G. and Zijlstra, R. T. 2003. Effect of pelleting and enzyme supplementation on variation in feed value of wheat-based diets fed to broiler chicks. Can. J. Anim. Sci. 83: 257-263. The effect of wheat cultivar, pelleting, and enzyme supplementation was measured with a broiler chick bioassay comparing differences in feed intake, growth, FCR and metabolisable energy (ME) level. Samples of two wheat cultivars from each of six classes were ground and were either unpelleted or pelleted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
1
4
1
Order By: Relevance
“…It is generally known that the addition of exogenous enzymes to wheat-and maize-based diets increases digestibility of nutrients in broiler chickens (Scott et al, 2003). However, in the current study there were no significant changes in ileal nutritient digestibility owing to MIL or enzyme supplementation or their interactions in broiler chicken at 21 days of age.…”
Section: Discussioncontrasting
confidence: 78%
“…It is generally known that the addition of exogenous enzymes to wheat-and maize-based diets increases digestibility of nutrients in broiler chickens (Scott et al, 2003). However, in the current study there were no significant changes in ileal nutritient digestibility owing to MIL or enzyme supplementation or their interactions in broiler chicken at 21 days of age.…”
Section: Discussioncontrasting
confidence: 78%
“…Scott et al (2003) found high correlations (approximately 0.70) for AME and FCR between broilers fed pelleted or unpelleted wheat cultivars. Growth performance in this study was not a determinative criterion in assessing energy utilization as it was not affected, despite distinct differences in energy utilization due to phytase supplementation.…”
Section: 37cdmentioning
confidence: 96%
“…Heat processing of cereals gelatinizes starch to some extent (Medel et al 2000), facilitating its endogenous enzymatic degradation, and solubilizes fiber components that might enhance the activity of exogenous enzymes (VukicVranjes and Wenk 1995). In addition, Scott et al (2003) demonstrated that pelleting destroyed endogenous phytase and NSP enzymes in wheat-based diets and increased the levels of soluble NSP, but did not improve performance of broilers, possibly explained by changes in the water hydration rate in the gut. A faster water hydration rate may enable broilers to increase nutrient intake by increasing the rate of diet passage (Scott et al 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Herstad and McNab (1975) concluded that HP of barley did not have any effect on performance of broilers at any age. Scott et al (2003) demonstrated that pelleting destroyed endogenous phytase and NSP enzymes in wheat-based diets and increased the levels of soluble NSP, but did not improve performance of broilers, possibly explained by changes in the water hydration rate in the gut. Autoclaving rye greatly potentiated the growth response to dietary pentosanase while producing little or no effect without enzymes (Teitge et al 1991).…”
Section: Introductionmentioning
confidence: 99%